Do Women Directors Representation Matter? Analyzing Its Moderating Effect on Firm Size and Cash Holdings - Nor Rahma Rizka; Deafatunnizwa Ulfida; Fitra Izzadieny (International Journal of Management and Business, 2025)
This research is based on the underrepresentation of female directors and its potential implications, particularly how their presence may moderate the relationship between firm size and cash holdings, given the gender gap and its potential impact on financial decision-making dynamics. This study aims to test and analyze the effect of company size on cash holdings with female director representation as a moderating variable in the LQ45 index company listed on the Indonesia Stock Exchange. The population used in this study is all companies listed in LQ45 index. Sample selection techniques using purposive sampling, with specified criteria, namely; Companies that are used as samples must be included in the LQ45 index since 2021-2023 in a row, the LQ45 company presents an annual report since 2021-2023. From all companies consistently included in the LQ45 index during the 2021-2023 period that provided the required financial indicators and annual reports, an initial sample of 31 companies was obtained. After excluding outliers, the final dataset comprised 69 observations for analysis. This study utilizes panel data to test the relationship between variables that are the focus of the study. The data obtained are processed, grouped, and analyzed using STATA statistical software. To test the moderation effect in the study, the Moderated Regression Analysis (MRA) method is used. The results found that company size has a significant positive effect on cash holdings, this study also indicates that female directors moderate the relationship between company size and cash holdings effectively. For future research could Investigate the relationship between gender diversity and cash management in different industries or international settings to assess the generalizability of the results, incorporate qualitative methods, such as interviews or case studies, to better understand how female directors influence financial decision-making and the organizational dynamics involved.